SYNTHESIS OF POLYETHERSULFONE/POLYVINYL ACETATE BLEND MEMBRANE INCORPORATED WITHTITANIUM DIOXIDE NANOPARTICLES FOR CO2/CH4SEPARATION - ABDULLAH, MOHD AFZAN (2020)
Polymer blend membrane (PBM)is providing analternative to single polymeric membranes as it consolidates the characteristics of both polymers into a new membrane material. However, most PBMs are experiencing blend incompatibility which results in unsatisfactory physico-chemical properties as well as separation performance. The main objective of this research is to study the effect of incorporating titanium dioxide(TiO2)at various nanoparticle concentrations (5 to 25wt.%) as inorganic filler during the synthesis polyethersulfone/polyvinyl acetate (PES/PVAc) blend membrane. The synthesized polymer blend mixed matrix membranes(PBMMMs)were characterized and their performances were evaluated in term of permeabilityand selectivity.